A photo-cleavable biotin affinity tag for the facile release of a photo-crosslinked carbohydrate-binding protein. Issue 6 (15th March 2016) - Chang, Tsung-Che; Adak, Avijit K.; Lin, Ting-Wei; Li, Pei-Jhen; Chen, Yi-Ju; Lai, Chain-Hui; Liang, Chien-Fu; Chen, Yu-Ju; Lin, Chun-Cheng
Graphical abstract: Abstract: The use of photo-crosslinking glycoprobes represents a powerful strategy for the covalent capture of labile protein complexes and allows detailed characterization of carbohydrate-mediated interactions. The selective release of target proteins from solid support is a key step in functional proteomics. We envisaged that light activation can be exploited for releasing labeled protein in a dual photo-affinity probe-based strategy. To investigate this possibility, we designed a trifunctional, galactose-based, multivalent glycoprobe for affinity labeling of carbohydrate-binding proteins. The resulting covalent protein–probe adduct is attached to a photo-cleavable biotin affinity tag; the biotin moiety enables specific presentation of the conjugate on streptavidin-coated beads, and the photolabile linker allows the release of the labeled proteins. This dual probe promotes both the labeling and the facile cleavage of the target protein complexes from the solid surfaces and the remainder of the cell lysate in a completely unaltered form, thus eliminating many of the common pitfalls associated with traditional affinity-based purification methods.